2021
DOI: 10.1002/hbm.25393
|View full text |Cite
|
Sign up to set email alerts
|

The default mode network and cognition in Parkinson's disease: A multimodal resting‐state network approach

Abstract: Involvement of the default mode network (DMN) in cognitive symptoms of Parkinson's disease (PD) has been reported by resting-state functional MRI (rsfMRI) studies. However, the relation to metabolic measures obtained by [18F]fluorodeoxyglucose positron emission tomography (FDG-PET) is largely unknown. We applied multimodal resting-state network analysis to clarify the association between intrinsic metabolic and functional connectivity abnormalities within the DMN and their significance for cognitive symptoms i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 74 publications
(86 reference statements)
4
28
0
Order By: Relevance
“…The PCC is a key region of the DMN with strong connectivity in primates with entorhinal cortex, parahippocampal gyrus, and, thus, hippocampal memory system, which is involved in autobiographical memory and imagining the future; and spatial navigation and scene processing (Leech and Sharp, 2014). Several prior studies have reported disrupted functional connectivity of the DMN in patients with PD by resting-state fMRI (Guo et al, 2021;Shang et al, 2021b;Wang et al, 2021) or fluorodeoxyglucose positron emission tomography (FDG-PET) (Ruppert et al, 2021;Schindlbeck et al, 2021;Shang et al, 2021a). However, how DMN dysfunction draws a relationship to cognitive symptoms in patients with PD still remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The PCC is a key region of the DMN with strong connectivity in primates with entorhinal cortex, parahippocampal gyrus, and, thus, hippocampal memory system, which is involved in autobiographical memory and imagining the future; and spatial navigation and scene processing (Leech and Sharp, 2014). Several prior studies have reported disrupted functional connectivity of the DMN in patients with PD by resting-state fMRI (Guo et al, 2021;Shang et al, 2021b;Wang et al, 2021) or fluorodeoxyglucose positron emission tomography (FDG-PET) (Ruppert et al, 2021;Schindlbeck et al, 2021;Shang et al, 2021a). However, how DMN dysfunction draws a relationship to cognitive symptoms in patients with PD still remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that [C-11]-PE2I (N-(3-iodoprop-2E-enyl)-2b-carbomethoxy-3b-(4-methyl-phenyl)nortropane) (PE2I), a PET radiotracer targeting neuronal dopamine (DA) transporters with high specificity, avidity in the caudate, putamen, and pallidum was indicative of more severe cognitive function deficits ( Ivanidze et al, 2020 ). Moreover, PET imaging of glucose metabolism has shown lower levels of metabolic activity in the parietal, temporal, cingulate, and frontal cortices of patients with PD-MCI and PDD ( González-Redondo et al, 2014 ; Ruppert et al, 2021 ). The cholinergic system, which is responsible for cognitive processing and is associated with the clinical manifestations of PDD, plays an important role in the structural and functional remodeling of the cortical circuits ( Aarsland et al, 2017 ).…”
Section: Clinical Features Of Parkinson’s Disease Mild Cognitive Impairment and Parkinson’s Disease’s Disease Dementiamentioning
confidence: 99%
“…Therefore, these prominent findings are meaningful for the elucidation of pathophysiological course within motor loop in PD. Higher dReHo in precuneus and MTG, the major components of the DMN engaged in internally directed cognition, 52 were monitored along with the decreasing trend of CBF, resulting to the deviated CBF/ReHo ratio. This finding was supported by previous reports that revealed neuronal excitability 48 or hypoperfusion 53 in DMN.…”
Section: Discussionmentioning
confidence: 99%